Carcinosarcoma of the Gallbladder with Chondrosarcomatous Differentiation and Intracytoplasmic Eosinophilic Hyaline Globules (Thanatosomes): A Report of a Case and Review of the Literature - Jumana A. Alratroot; Amani A. Joudeh; Samir S. Amr (Hindawi Limited, 2019)
A 52-year-old woman presented with abdominal pain and vomiting. Computed tomography (CT) scan of the abdomen revealed a huge exophytic gallbladder mass displacing or invading the surrounding structures. The patient underwent radical cholecystectomy, transverse colectomy, distal gastrectomy, and liver bed resection. Histologically, the tumor showed both carcinomatous and sarcomatous components, with prominent chondrosarcomatous differentiation. In addition, several malignant cells showed intracytoplasmic eosinophilic hyaline globules (Thanatosomes). The tumor showed metastatic deposits to the omentum, the liver, and the peripancreatic lymph nodes. We report this unusual case and present a review of all cases of carcinosarcoma of the gallbladder with chondrosarcomatous differentiation.